PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN WORK ENGAGEMENT TERHADAP KINERJA PENGURUS PARTAI X KOTA SURABAYA - Rizaky, Muhammad Udhan; Iryanti, Endang (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to determine the influence of transformational leadership style and work engagement on the performance of Party X administrators in Surabaya City. The research employs a quantitative approach, with data collected through questionnaires distributed to 43 respondents using a saturated sampling technique. The collected data were analyzed using Smart PLS software. The results of the study indicate that transformational leadership style has a positive and significant effect on performance, and work engagement also has a positive and significant effect on performance.